2010
DOI: 10.1007/s10600-010-9735-x
|View full text |Cite
|
Sign up to set email alerts
|

Indole alkaloids from the roots of Isatis ingigotica and their antiherpes simplex virus type 2 (HSV-2) activity in vitro

Abstract: A new indole alkaloid 1, together with four known indole alkaloids 2-5, was isolated from the 95% EtOH extract of the traditional Chinese medicinal plant Isatis indigotica. Alkaloids 2-5 were found in the plant for the first time. Their structures were elucidated as 3-hydroxy-3-acetonitrile-4-hydroxy-2-indolone (1), 1-methoxy-3-indoleacetonitrile (2), 3-indoleacetic acid (3), 3-indolealdehyde (4), and 1-methoxy-3-indolecarbaldehyde (5) on the basis of spectroscopic data. Their anti-HSV effects in vitro were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The major active compounds isolated from this species comprise terpenoids, lignans, and indole alkaloids [14][15][16][17] . These compounds were confirmed to have antiviral 18,19 , antibacterial 20 , anti-inflammatory 21,22 , and antileukemia 23,24 functions. Previous studies based on transcriptomes revealed a few candidate genes involved in the biosynthesis of active compounds in this species [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 88%
“…The major active compounds isolated from this species comprise terpenoids, lignans, and indole alkaloids [14][15][16][17] . These compounds were confirmed to have antiviral 18,19 , antibacterial 20 , anti-inflammatory 21,22 , and antileukemia 23,24 functions. Previous studies based on transcriptomes revealed a few candidate genes involved in the biosynthesis of active compounds in this species [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 88%
“…Their common names are “Da-Qing-Ye”and “Ban-Lan-Gen”, respectively, in the Chinese Pharmacopeia [1] . Previous studies have shown that Da-Qing-Ye and Ban-Lan-Gen have a wide range of pharmacological bioactivities, including antivirus [2] , [3] , [4] , anti-bacterial [5] , anti-endotoxic [6] , antitumor [7] , anti-inflammatory [8] , [9] and immune regulatory effects [10] . Chemical research indicated that Da-Qing-Ye contains a substantial amount of alkaloids [4] , [11] , [12] , [13] , organic acids [14] , nucleosides [15] , ignanoids [16] , quinoline and quinazolone [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Natural substances offer an interesting pharmacological perspective for the development of novel antiviral drugs with broad-spectrum antiviral properties and novel modes of action. Some natural indole alkaloid compounds have been proven to have antiviral potential against dengue virus and HSV-2 [ 23 , 24 ]. In this study, we report novel findings that pimprinethine, WS-30581 A and WS-30581B, as natural indole alkaloids, were effective inhibitors of the replication of EV71 and ADV-7, with slight inhibitory activity against CVB3, HSV-1 and H1N1 (with a few exceptions).…”
Section: Discussionmentioning
confidence: 99%